Knowledge base for the systematic design of wet cooling towers. Part I: Selection and tower characteristics - Mohiuddin, A. K. M.; Kant, K. (Elsevier Science Ltd and IIR, 1996)
This paper describes part of the detailed methodology for the thermal design of wet, counterflow and crossflow types of mechanical and natural draught cooling towers. Starting with a brief introduction, an attempt is made here to present different steps of cooling tower design. The steps include: selection of a cooling tower; determination of tower characteristic ratio; computation of moist air properties; determination of the ratio of the water-to-air loading; integration procedure for the tower characteristic ratio. The design of a cooling tower needs the use of different logical decisions, empirical relations and assumptions. The choice of a proper tower and its proper design would increase its efficiency and help conserve energy.